Multicomponent Synthesis of Bicyclic Thiazolidinethiones and Oxazolidinones in Water. Issue 4 (22nd November 2013) - Stalling, Timo; Pauly, Jan; Schmidtmann, Marc; Martens, Jürgen
Abstract: A powerful three‐component reaction for the synthesis of bicyclic thiazolidinethiones and oxazolidinones at room temp. in water, starting from readily available amines, chloroacetaldehyde, and CS2 /CO2, is described. A simple one‐pot procedure allows the construction of two new cyclic systems and four new bonds, with all reactants being efficiently utilized in this transformation. KHCO3 is used as a productive source of CO2 . Broad potential for derivatization is demonstrated. Abstract : A new water‐mediated multicomponent reaction for producing bicyclic thiazolidinethiones and oxazolidinones from commercially available bifunctional amines, chloroacetaldehyde, and CS2 /CO2 was developed. The new procedure uses extremely mild conditions and KHCO3 as CO2 source. In some cases the products were isolated in excellent yields by simple extraction without requiring further purification.